PERAN KOMUNIKASI ANTARA KARYAWAN DENGAN CUSTOMER DALAM MENCIPTAKAN CUSTOMER LOYALTY TITIK DUA KOPI KEDUNGMUNDU - Naufal Eksan Pratama; Nadia Itona Siregar (STIE Wiyatamandala, 2023)
The problems studied were various complaints coming from customers stating that the customer was dissatisfied with the service attitude provided by Titik Dua Kopi Kedungmundu employees. The purpose of this study was to describe how interpersonal communication between employees and customers creates customer loyalty at Titik Dua Kopi Kedungmundu Semarang. This study uses a qualitative research method with a constructivism paradigm using a case study approach. The data collection technique was through interviews with several informants, namely the Operational Manager of Titik Dua Kopi Kedungmundu, Titik Dua Kopi Kedungmundu Employees and customers. Qualitative data analysis techniques using Nvivo 12 pro software. The results of this study there are seven characteristics of interpersonal communication in creating customer loyalty namely support, openness, equality, curiosity, empathy, caring, positive attitude.